NUCLEAR POWER PLANTS SAFETY IMPROVEMENT PROJECTS RANKING - Григорян, Анна Сергеевна; Григорян, Тигран Георгиевич; Квасневский, Евгений Анатольевич (Eastern-European Journal of Enterprise Technologies, 2013)
The ranking nuclear power plants safety improvement projects is the most important task for ensuring the efficiency of NPP project management office work. Total amount of projects in NPP portfolio may reach more than 400. Features of the nuclear power plants safety improvement projects ranking in NPP portfolio determine the choice of the decision verbal analysis as a method of decision-making, as it allows to quickly compare the number of alternatives that are not available at the time of constructing decisive rule, take into account qualitative criteria for the evaluation of projects, gradually establish the preferences of the decision maker. The model for ranking process, the system of assessment criteria and the scale of verbal assessments gradations of projects quality is presented. On the basis of specified criteria and scales the united ordinal scale of assessment and ranking of nuclear power plants safety improvement projects is developed. Further research should be directed at the improvement of the proposed system of criteria and scales for different types of nuclear power plants safety improvement projects.